Preparation of Transparent Film of Layered Double Hydroxide with Anionic Pyrene Derivatives and Its Luminous Toluene Detection Ability - Takuya Fujimura; Yoshiya Akagashi; Yu-hei Aoyama; Ryo Sasai (International Journal of Photoenergy)
To prepare the transparent solid film of layered double hydroxide, the filtration-film transfer (FFT) method using LDH nanosheet colloidal suspension was investigated. It was found that the homogeneous LDH solid film with enough transparency in the visible light range could be prepared by the FFT method. Moreover, anionic pyrene (Pyr−) molecules could be incorporated into the transparent LDH solid film by immersing in anionic pyrene solution. From both absorption and emission spectra of the transparent Pyr−/LDH solid film, Pyr− incorporated in the LDH solid film formed aggregates and mainly showed the strong excimer emission. Additionally, the luminous response of the transparent Pyr−/LDH solid film was investigated in ethanol-toluene mixed solution with various toluene contents. As results, the ratio of luminescence intensities from static excimer and monomer of incorporated Pyr− molecules depended on the toluene content, and excimer emission decreased with an increase in the toluene content. This luminous response can be caused by an increase of the monomeric Pyr− species, because Pyr− aggregates are broken by adsorption of toluene molecules into the LDH interlayer space. The obtained transparent hybrid film may be useful as a detectable material of toluene in solvent by luminous change.